Challenges in the quest to create global qualifications and standards are driving change in education systems (Economic and Political Thought, 2012)
The article presents challenges and tasks of human capital marketfor national education systems resulting in student mobility, increasedparticipation and the need for standards and comparability of qualifications.Moreover, the author discusses the example of the United Kingdom, whichcan also refer to the situation in other countries, and he states that theachievement of minimum standards is no longer sufficient for the Britishuniversities because they need higher and higher standards in order tocontinue attracting foreign students who pay full fees, which the universitiesdepend on as they constitute a considerable part of their finances.